Optimasi Sifat Mekanik dan Morfologi Permukaan Campuran Resiprena dengan Matriks Polimer Polipropilena dan Polistirena melalui Penambahan Stearin - Ayu Syufiatun Br Tarigan; Nina Hartati; Basuki Wirjosentono; Arbaiyah Arbaiyah; Anjar Siti Mashitoh (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to investigate the effect of adding resiprene and stearic acid on the mechanical properties and surface morphology of polyolefin blends, specifically polypropylene (PP) and polystyrene (PS). Resiprene was incorporated as an additive to enhance flexibility, while stearic acid was introduced to improve polymer compatibility and blend dispersion. The test results showed that the addition of 20 phr resiprene to polypropylene yielded the highest tensile strength of 9.63 MPa and an elongation of 5.85%, indicating high flexibility and compatibility of the blend. In contrast, the tensile strength of the PS-based blends was generally lower than that of the PP-based counterparts. The addition of 1 phr stearic acid proved effective in reducing the number of pores on the surface of both PP and PS blends. Interestingly, the PS-resiprene-stearic acid blend exhibited a more refined surface morphology compared to the PP-resiprene-stearic acid blend, suggesting higher compatibility of PS within the composite system.